Causes of abortion in Iranian sheep flocks and associated risk factors - Hossein Esmaeili; Amir Pasha Shakeri; Zia Nosrati Rad; Ehsan Baghal Arani; Sergio Villanueva-Saz; Héctor Ruiz; Delia Lacasta (Veterinary Research Communications, 2022)
Abortion is a major issue in sheep husbandry. It can result in significant economic losses and a severe public health risk. This survey assessed the infectious and non-infectious causes of abortion in Iranian sheep flocks and determined the main risk factors. In this cross-sectional survey, causes of abortion were evaluated in 757 sheep flocks, and risk factors were analysed. A checklist containing general animal information for each abortion outbreak evaluated was filled in. Data were analysed using univariate tests and multivariable binary logistic regression analysis. In this sense, parity, gestational age of the aborted fetus, vaccination protocol, mineral supplementation and history of stillbirth showed significant associations with abortion. Infectious agents such as Coxiella burnetti (22.7%), Chlamydia abortus (12.3%) and Brucella melitensis (10.4%) were the most frequently isolated in the investigated flocks, with more than 2% of abortion rates. On the other hand, non-infectious agents such as trauma, pregnancy toxaemia and vitamin E/Se deficiency were involved in those flocks with low abortion rates (less than 10%). Results revealed multiple causes of abortion outbreaks among Iranian sheep flocks, which need careful investigation to identify possible aetiology and risk factors. Further studies are necessary to evaluate if these factors are similar to other countries in the same region.